The empirical study of a four-row heat pipe heat exchanger to predict the year-round energy recovery in the tropics - Yau, Yat Huang; Ahmadzadehtalatapeh, Mohammad (SAGE Publications, 2011)
The effect of heat pipe heat exchanger on the heat recovery was studied in the tropics. The performance of the heat exchanger was monitored during the one week of operation (168-h) to find out the performance characteristic curves. Three coil face velocities namely, 2, 2.2 and 2.5m/s were tested and the temperature of return air was controlled at 24°C. The relevant empirical equations were then employed for the hour-by-hour prediction of the energy recovery by the heat pipe heat exchanger for the whole year. The impact of inside design temperature on the heat recovery by the heat exchanger was also studied. The thermal performance of the heat pipe heat exchanger was simulated based on the effectiveness-NTU method and the theoretical values were compared with the experimental data.Practical application: Performance improvement of the heating, ventilating and air conditioning systems is a challenge to the designers. The results obtained from this research work could serve as a practical guide for engineers who are intending to use heat pipe heat exchangers in the heating, ventilation and air conditioning systems operating in tropical climates. Engineers and researchers have the potential to use the recommended empirical performance equations to examine the impact of heat pipe heat exchangers on the performance of the current air conditioning systems. Moreover, these empirical performance equations enable the year-round operating effect of heat pipe heat exchangers on energy savings to be predicted realistically. © The Chartered Institution of Building Services Engineers 2009.